2022
DOI: 10.5194/acp-22-8151-2022
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of active satellite sensors' low-level cloud detection limitations on cloud radiative forcing in the Arctic

Abstract: Abstract. Previous studies revealed that satellites sensors with the best detection capability identify 25 %–40 % and 0 %–25 % fewer clouds below 0.5 and between 0.5–1.0 km, respectively, over the Arctic. Quantifying the impacts of cloud detection limitations on the radiation flux are critical especially over the Arctic Ocean considering the dramatic changes in Arctic sea ice. In this study, the proxies of the space-based radar, CloudSat, and lidar, CALIPSO (Cloud-Aerosol Lidar and Infrared Pathfinder Satellit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 65 publications
(70 reference statements)
0
2
0
Order By: Relevance
“…Third, the lowest levels from CloudSat's vertical profiles suffer from ground clutter due to reflections at the surface called blind zone. This blind zone prevents the cloud assessment roughly below the first kilometer (Palerme et al, 2019;Lamer et al, 2020;Liu, 2022). Using ground-based radar measurements as reference, Maahn et al (2014) showed that CloudSat underestimates the total precipitation by 9 percent points (pp) over Ny-Ålesund, Svalbard.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, the lowest levels from CloudSat's vertical profiles suffer from ground clutter due to reflections at the surface called blind zone. This blind zone prevents the cloud assessment roughly below the first kilometer (Palerme et al, 2019;Lamer et al, 2020;Liu, 2022). Using ground-based radar measurements as reference, Maahn et al (2014) showed that CloudSat underestimates the total precipitation by 9 percent points (pp) over Ny-Ålesund, Svalbard.…”
Section: Introductionmentioning
confidence: 99%
“…CloudSat observations have been compared with airborne remote sensing (e.g., Gayet et al, 2009;Painemal et al, 2019) for relatively homogeneous clouds at higher altitudes to calibrate airborne instruments (Barker et al, 2008;Protat et al, 2009Protat et al, , 2011. For the first time, Liu (2022) investigates synthetic CloudSat cloud masks in the Arctic region. These data are based on radar reflectivities from QuickBeam radar forward simulations (Haynes et al, 2007) that used vertical profiles of retrieved cloud properties from ground-based radar and lidar during the SHEBA (Surface Heat Budget of the Arctic Ocean) experiment.…”
Section: Introductionmentioning
confidence: 99%